Cell–collagen interactions: the use of peptide Toolkits to investigate collagen–receptor interactions. (20th March 2008) - Farndale, Richard W.; Lisman, Ton; Bihan, Dominique; Hamaia, Samir; Smerling, Christiane S.; Pugh, Nicholas; Konitsiotis, Antonios; Leitinger, Birgit; de Groot, Philip G.; Jarvis, Gavin E.; Raynal, Nicolas
Abstract : Fibrillar collagens provide the most fundamental platform in the vertebrate organism for the attachment of cells and matrix molecules. We have identified specific sites in collagens to which cells can attach, either directly or through protein intermediaries. Using Toolkits of triple-helical peptides, each peptide comprising 27 residues of collagen primary sequence and overlapping with its neighbours by nine amino acids, we have mapped the binding of receptors and other proteins on to collagens II or III. Integrin α2β1 binds to several GXX′GER motifs within the collagens, the affinities of which differ sufficiently to control cell adhesion and migration independently of the cellular regulation of the integrin. The platelet receptor, Gp (glycoprotein) VI binds well to GPO (where O is hydroxyproline)-containing model peptides, but to very few Toolkit peptides, suggesting that sequence in addition to GPO triplets is important in defining GpVI binding. The Toolkits have been applied to the plasma protein vWF (von Willebrand factor), which binds to only a single sequence, identified by truncation and amino acid substitution within Toolkit peptides, as GXRGQOGVMGFO in collagens II and III. Intriguingly, the receptor tyrosine kinase, DDR2 (discoidin domain receptor 2) recognizes three sites in collagen II, including its vWF-binding site, although the amino acids that support the interaction differ slightly within this motif. Furthermore, the secreted protein BM-40 (basement membrane protein 40) also binds well to this same region. Thus the availability of extracellular collagen-binding proteins may be important in regulating and facilitating direct collagen–receptor interaction.